2020
DOI: 10.1021/acsami.0c10282
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Strong Antioxidative, Therapeutic Nanoparticles Based on Amino Acid-Induced Ultrafast Assembly of Tea Polyphenols

Abstract: Nanoformulations offer the opportunity to overcome the shortcomings of drug molecules, such as low solubility, side effects, insufficient stability, etc., but in most of the current nanomedicines, nanocarriers as excipients do not directly participate in the therapy procedure. Accordingly, it is promising to develop the nanotherapeutics composed entirely of pharmaceutically active molecules. Tea polyphenols, especially epigallocatechin gallate (EGCG), are a kind of natural antioxidants with various biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 67 publications
6
100
0
Order By: Relevance
“…In our previous work, we reported that high doses of EGCG pure nanocarriers had good antitumor effects in vivo. 32 In this work, the antitumor effect of R-GCS/DOX nanodrugs prepared by the reassembly of polyphenol CSs was also better than that of free DOX, which again proved that catechin can enhance the antitumor ability of the drug, showing the advantages of using therapeutic molecules to construct nanomedicines. As shown in Figure S12, HE sections of heart, liver, lung, and kidney in all groups showed normal tissue structure and no lesions.…”
Section: ■ Results and Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…In our previous work, we reported that high doses of EGCG pure nanocarriers had good antitumor effects in vivo. 32 In this work, the antitumor effect of R-GCS/DOX nanodrugs prepared by the reassembly of polyphenol CSs was also better than that of free DOX, which again proved that catechin can enhance the antitumor ability of the drug, showing the advantages of using therapeutic molecules to construct nanomedicines. As shown in Figure S12, HE sections of heart, liver, lung, and kidney in all groups showed normal tissue structure and no lesions.…”
Section: ■ Results and Discussionsupporting
confidence: 61%
“…The average weight of the spleen in the control group was 0.77 g, while that in the DOX group was 0.073 g and R-GCS/DOX was 0.059 g (Figure e,f). In our previous work, we reported that high doses of EGCG pure nanocarriers had good antitumor effects in vivo . In this work, the antitumor effect of R-GCS/DOX nanodrugs prepared by the reassembly of polyphenol CSs was also better than that of free DOX, which again proved that catechin can enhance the antitumor ability of the drug, showing the advantages of using therapeutic molecules to construct nanomedicines.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…30% of its dry leaf weight, and also collectively referred to as catechins. The biological bioactivities of TP with epigallocatechin gallate (EGCG) as the primary contributor have been well documented, such as antioxidation, anticancer, inhibiting human stone formation, and reducing the risk of degenerative diseases. The use of TP or EGCG as the active molecule either for direct encapsulation or for fabricating functional nanomaterials is now a hot theme in the field of nutrition and pharmaceutical science. The combination of keratin and TP is expected to give rise to the composite biomaterials with salient features potentially for various biomedical purposes.…”
Section: Introductionmentioning
confidence: 99%